Optimized Circulating Current Control and Enhanced AC Fault Ride-through Capability Using Model Predictive Control for MMC-HVDC Applications - Jahangeer Badar Soomro; Faheem Akhtar Chachar; Madad Ali Shah; Abdul Aziz Memon; Faisal Alsaif; Sager Alsulamy (Energies, 2023)
This paper presents a novel model predictive control (MPC) approach for suppressing circulating currents in MMC-based HVDC systems. The proposed MPC eliminates the need for PI-regulators and pulse width modulators, resulting in improved dynamic response and controllability. The methodology demonstrates exceptional efficacy in controlling output current and addressing voltage ripple concerns associated with sub module (SM) capacitors. An innovative, communication-free fault ride-through (FRT) method is also introduced, eliminating the need for a DC chopper and ensuring rapid recovery following faults. To overcome the computational challenges associated with the traditional MPC algorithm, an aggregate model of the MMC is proposed, significantly reducing predicted states, hardware requirements, and calculations. Simulations validate the robustness of the proposed MPC control algorithm in tracking AC side current, suppressing circulating current, and regulating capacitor voltages under various scenarios. Future research will explore system expansion, integration with renewable energy sources, and hardware-in-loop setup testing for further validation.